Crimean Congo hemorrhagic fever - description of family epidemic - Radoslav Katanić; Nataša Katanić; Dijana Mirić; Bojana Kisić; Ksenija Bojović; Dragica Odalović; Andrijana Odalović (Биомедицинска истраживања, 2013)
Background . Crimean Congo hemorrhagic fever (CCHF) is an acute, viral, natural, focal zoonosis, which is under natural conditions transferred to man by the bite of certain species of ticks. There is also inter-human transmission of infection. A clinical picture is characterized by temperature and severe hemorrhages of different localization and different intensity. In this paper family epidemics of Crime an-Congo hemorrhagic fever are described. Epidemic description . Treating patients with Crimean-Congo hemorrhagic fever in Clinic of Infectious Diseases in Pristina we observed six family outbreaks. In four epidemics two family members were affected, in one four and in the other six members. In all patients the disease was manifested with tem perature and bleeding. In both families in which four and six people were affected, one lethal outcome appeared. Diagnosis of Crimean-Congo hemorrhagic fever was made on the basis of epidemiological, clinical and serological data. Conclusion: . Crimean-Congo hemorrhagic fever is characterized by fever and hemorrhages. It occurs sporadically or in small, often family outbreaks. Although it is a zoonosis, inter-human transmission occurs, which is of great epidemiological importance.
Keywords: Crimean Congo hemorrhagic fever; human transmission